Safe and Learning in the Midst of Fragility, Conflict, and Violence : A World Bank Group Approach Paper - World Bank (Washington, DC, 2022)
Education is one of the most powerful forces we have for creating a more peaceful and prosperous future. Yet the children most in need of a good education are also at greatest risk of having their learning disrupted, whether by conflict, violence, pandemics, climate, or other crises. This approach paper lays out the World Bank’s policy approach for how to deliver education services so that children are safe and learning. The first section defines the context, dynamics, and key terms and concepts of education in fragility, conflict, and violence (FCV). The second section traces the evolution of the World Bank’s strategy for delivering education services in fragile settings. It draws on interviews with organizations working on education in emergency situations and presents the World Bank portfolio trends for FCV in education, dating back to 2005. The third section presents operational recommendations, drawing on interviews with World Bank task team leaders, managers, and country directors, as well as key partners. As such, this paper is not a systematic review of what works in FCV situations. Rather, it presents guiding principles, policy options, and operational recommendations for how the education sector can help deliver on the Bank Group’s FCV Strategy.